2001
DOI: 10.1007/s11745-001-0836-z
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐10,Cis‐12 conjugated linoleic acid reduces triglyceride content while differentially affecting peroxisome proliferator activated receptor γ2 and aP2 expression in 3T3‐L1 preadipocytes

Abstract: A series of experiments was conducted using 3T3-L1 preadipocytes as the cell model to determine: (i) whether the triglyceride (TG)-lowering effects of a crude mixture of conjugated linoleic acid (CLA) isomers were due to a specific isomer of CLA and the timing of treatment, (ii) if CLA reduced TG content by inhibiting a key regulator of adipogenesis, (iii) if CLA incorporated into either neutral lipid or phospholipid cell fractions, and (iv) whether the effects of CLA treatment were reversible. Trans-10,cis-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 33 publications
(61 reference statements)
10
62
1
7
Order By: Relevance
“…75,76 A similar study in cows has shown that supplementation with 100 g/day of CLA for 1 day decreased fatty acid synthesis and desaturation. 77 Supporting data have been reported by other studies using the cultures of human preadipocytes 48,78,79 and stromal vascular cells from human adipose tissue. 80 Data from the above studies collectively suggest that CLA decreases triglyceride content, in part, by decreasing fatty acid synthesis, uptake and esterification into triglyceride by adipocytes, at least in certain species and model systems.…”
Section: Conjugated Linoleic Acid and Obesitymentioning
confidence: 64%
“…75,76 A similar study in cows has shown that supplementation with 100 g/day of CLA for 1 day decreased fatty acid synthesis and desaturation. 77 Supporting data have been reported by other studies using the cultures of human preadipocytes 48,78,79 and stromal vascular cells from human adipose tissue. 80 Data from the above studies collectively suggest that CLA decreases triglyceride content, in part, by decreasing fatty acid synthesis, uptake and esterification into triglyceride by adipocytes, at least in certain species and model systems.…”
Section: Conjugated Linoleic Acid and Obesitymentioning
confidence: 64%
“…A ativação de PPAR γ 2 pelo CLA, particularmente pelo isômero trans-10, cis-12, tem sido demonstrada em cultura de adipócitos 3T3-L1 de roedores, como mecanismo responsável pela redução da composição corporal 118,136 . É importante ressaltar que, segundo Evans et al 137 , a ativação de PPAR γ 2 pelo trans-10, cis-12 CLA modularia o efeito redutor da gordura corporal em curto prazo (48h), visto que os autores observaram inibição de PPAR γ 2 quando o tempo de contato com o CLA aumentou (6 dias).…”
Section: Cla E Receptores Ativados Por Proliferadores De Peroxissomounclassified
“…É importante ressaltar que, segundo Evans et al 137 , a ativação de PPAR γ 2 pelo trans-10, cis-12 CLA modularia o efeito redutor da gordura corporal em curto prazo (48h), visto que os autores observaram inibição de PPAR γ 2 quando o tempo de contato com o CLA aumentou (6 dias). A maioria dos estudos objetivando buscar os alvos moleculares da ação redutora da gordura corporal pelo CLA em adipócitos, reúne dados que permitem concluir que a inibição de PPAR γ, particularmente pelo trans-10, cis-12 CLA, levaria à redução da gordura corporal pela modulação da expressão gênica no sentido de inibir a diferenciação celular e alterar a atividade de proteínas envolvidas na lipogênese e na lipólise 109,136 . É importante a ressalva de que, nos estudos citados anteriormente, o tempo de exposição dos adipó-citos aos isômeros de CLA até os efeitos serem observados foi superior a 5 dias, confirmando que, em longo prazo, segundo Evans et al 136 , o efeito do trans-10, cis-12 CLA é de fato inibir PPAR γ. Um dado interessante é o do trabalho de Brown et al 138 , segundo o qual quando as células foram expostas ao isômero cis-9, trans-11, houve aumento de PPAR γ e, conseqüentemente, das proteínas codificadas pelos genes que estão sob seu controle transcricional, promovendo a adipogê-nese.…”
Section: Cla E Receptores Ativados Por Proliferadores De Peroxissomounclassified
“…Adipose differentiation is a complex process by which fibroblast-like undifferentiated cells are converted into cells that accumulate lipid droplets [2]. It has been reported that PPARγ plays a critical role in adipogenesis [2] [3]. PPARγ is a nuclear hormone receptor that plays an essential role in lipid and glucose homeostasis and predominantly expressed in the adipose tissue [2].…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ is a nuclear hormone receptor that plays an essential role in lipid and glucose homeostasis and predominantly expressed in the adipose tissue [2]. Upon agonist binding, PPARγ drives the expression of several adipocyte-specific genes [3] such as FABP4 (fatty acid binding protein 4) and CD36 (scavenger receptor).…”
Section: Introductionmentioning
confidence: 99%